Jakie wody mineralne w XVIII i XIX w. pijali mieszkańcy Ostrowa Tumskiego w Poznaniu - Kowalczyk, Andrzej (Ecclesia. Studia z Dziejów Wielkopolski, 2012)
The drinking of mineral waters at Ostrów Tumski in Poznań is evidenced by fragments of stoneware bottles with preserved signatures - findings registered during archaeological excavations. Most of the discovered fragments come from 19th century bottles. Only about a dozen items represent containers from the 18th century - a majority of those are probably pieces of seltzer water bottles. In the 19th century the inhabitants of this island in Poznań drank mineral waters from springs located on the territory of today's Germany (Bad Kissingen, Niederselters, Bad Friedrichshall, Bad Ems) and Czechia (Bylany/Male Brezno, Frantiskovy Lazne, Bilina, Zajecic, Marianske Lazne).